1993
DOI: 10.1095/biolreprod48.6.1320
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Phosphate, Energy Substrates, and Amino Acids on Development of in Vitro-Matured, in Vitro-Fertilized Bovine Oocytes in a Chemically Defined, Protein-Free Culture Medium1

Abstract: Bovine oocytes that had been matured and fertilized in vitro were cultured in a simple, chemically defined, protein-free medium (mTLP-PVA). When the medium was supplemented with 19 amino acids, development to the 8-cell (14-20% vs. 38-46%), morula (0-6% vs. 27-32%), and blastocyst (0-1% vs. 9-13%) stages 96, 144, and 192 h after insemination, respectively, was significantly greater in the absence than in the presence of glucose (5.56 mM) regardless of the presence of phosphate (1.05 mM). However, blastocyst de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(83 citation statements)
references
References 34 publications
2
78
0
1
Order By: Relevance
“…Our results are consistent with other studies that show significant effect of EGF and myo-inositol on embryo developmental competence in bovine (Mtango et al 2003;Lim et al 2007). Another study reported that without phosphate, glucose alone had no detrimental effect on early embryonic development (Kim et al 1993). In contrast, Barnett and Bavister (1996) and Biggers and McGinnis (2001) showed that in culture media containing glucose, phosphate inhibited embryo development to blastocyst stage.…”
Section: Discussionmentioning
confidence: 98%
“…Our results are consistent with other studies that show significant effect of EGF and myo-inositol on embryo developmental competence in bovine (Mtango et al 2003;Lim et al 2007). Another study reported that without phosphate, glucose alone had no detrimental effect on early embryonic development (Kim et al 1993). In contrast, Barnett and Bavister (1996) and Biggers and McGinnis (2001) showed that in culture media containing glucose, phosphate inhibited embryo development to blastocyst stage.…”
Section: Discussionmentioning
confidence: 98%
“…The increase in oxidative activity observed in sperm-activated oocytes corresponds to the initiation of pronuclear formation and first mitotic division in putative zygotes, suggesting increased demands for energy for these events. It has been observed that one-and two-cell bovine embryos are dependent on mitochondrial oxidative phosphorylation for energy supply, consuming oxidative substrates to produce ATP (Kim et al 1993, Thompson et al 1996. Coincidently, a higher oxygen consumption rate was detected before cleavage in bovine zygotes (Lopes et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…They obtained consistent development of hamster embryos in vitro beyond the two-cell and four-cell stages to the blastocyst stage in a modified Tyrode's medium that did not contain glucose and phosphate (Schini and Bavister, 1988;McKieman and Bavister, 1990; Bavister, 1990;Seshagiri and Bavister, 1991a). This new medium, designated as hamster embryo culture medium 1 (HECM-1; Schini and Bavister, 1988), was applied to the culture of rat (Kishi et al, 1991) and bovine (Pinyopummintr and Bavister, 1991;Kim et al, 1993) one-cell embryos in which development to the blastocyst stage was supported to a limited extent. However, it is not clear whether phosphate and glucose affect rat embryo development independently or in combi¬ nation.…”
Section: Introductionmentioning
confidence: 99%